Robot adoption at German plants - Deng, Liuchun,Plümpe, Verena,Stegmaier, Jens (Halle Institute for Economic Research (IWH) - Member of the Leibniz Association, 2020)
Using a newly collected dataset with plant-level information of robot use from 2014 to 2018, we provide the first microscopic portrait of robotisation in Germany and study the potential determinants of robot adoption. Our descriptive analysis uncovers five stylised facts concerning both extensive and, perhaps more importantly, intensive margin of plant-level robot use: (1) Robot use is relatively rare with only 1.55% German plants using robots in 2018. (2) The robot distribution is highly skewed. (3) New robot adopters contribute substantially to the recent robotisation. (4) Robot users are exceptional along several dimensions of plant-level characteristics. (5) Heterogeneity in robot types matters. Our regression results further suggest that plant size, low-skilled labour intensity, and exporter status all have strong and positive effect on future probability of robot adoption. However, controlling for plant size, we find that plant-level productivity has no, if not negative, impact on robot adoption.
urn:nbn:de:gbv:3:2-127460
Keywords: Graue Literatur; robots; robot adoption; automation; labour; productivity; plant-level